Energy-efficient operation of diesel–electric locomotives using ahead path data. (January 2016) - Saadat, M.; Esfahanian, M.; Saket, M.H.
Abstract: Diesel–electric locomotives have significant fuel consumption. In this study, fuzzy look-ahead control is considered as an online approach for fuel consumption optimization. A fuzzy controller will modify the desired speed profile by accounting for the gradient and speed limits of the path ahead. Journey time increment is used as an optimization constraint. The existing models for train motion simulation are calculating the fuel consumption by an indirect index. A new model for train-movement simulation is proposed to calculate fuel consumption more accurately. This model considers the locomotive subsystems and satisfies the experimental fuel consumption data specified in the locomotive's catalog. Simulation of a train with a GM Sd40-2 on three local tracks showed considerable reduction in fuel consumption along with an acceptable journey time increment. Simulation results also showed that fuzzy look-ahead controller has very faster calculations in comparison with the controller based on the dynamic programming method. Highlights: Fuel consumption is calculated as a function of diesel engine's speed and torque. Fuzzy look-ahead control is implemented for fuel consumption optimization. Fuzzy look-ahead has faster calculation in comparison with dynamic programming.